QOLP-20. A FEASIBILITY STUDY UTILIZING MINDFULNESS MEDITATION DURING CONCOMITANT CHEMORADIATION IN MALIGNANT GLIOMA PATIENTS: HEALTH-REPORTED QUALITY OF LIFE (HRQOL) RESULTS. (9th November 2020) - Randazzo, Dina; Buckley, Evan; Herndon, James; Cort, Nicole; Affronti, Mary; Lipp, Eric; Desjardins, Annick; Johnson, Margaret; Landi, Daniel; Ashley, David; Friedman, Henry; Glass, Oliver; et al.
Abstract: BACKGROUND: Primary brain tumor patients experience high levels of distress due to their diagnosis and treatment leading to changes in their health-related quality of life (HRQoL). Even with the standard treatment of 6 weeks of radiation with concurrent temozolomide for malignant gliomas, the prognosis remains poor. We sought to provide a new intervention and coping skill for our patients during chemoradiation to alleviate some of their stress and anxiety. Mindfulness meditation is a mind-body therapy used in many other cancer groups which can alleviate stress and improve fatigue, cognition, and sleep. METHODS: 15 newly diagnosed malignant glioma subjects started 1-hour weekly phone mindfulness sessions during the 6 weeks of chemoradiation. They completed an in-person mindfulness session and interview upon return to the clinic with a final follow up survey 2 months later. Patient reported outcomes questionnaires were collected at each time point. RESULTS: 0/15 subjects completed their post-chemo/in-person visit, and 9 completed their final follow-up surveys 2 months later. Scores for perceived cognition, fatigue, sleep, anxiety, spiritual-well being and mindfulness improved over these time points. Completed HRQoL patient-reported outcome questionnaires with positive trends noted from the mean (SD) post-chemo/in-person visit change from baseline and the follow-up change from baseline were: FACT-Cog perceived Cognitive Impairments subscale 4.11(13.55), 9.14(16.77); FACT-G total -5.48(16.02), 7.02(13.44); FACT-Br total -3.15(24.76), 13.17(23.37); FACIT-F -5(7.68), 0(7.92); and the FACIT-Sp12 -1.38(7.6), 2.17(4.88). Trail making Part A completion times from baseline to follow up decreased over time in 8/9 subjects and 7/9 subjects in Part B. Per the final follow up survey, 7/9 subjects continued their meditation practices after the training sessions and subjectively noted benefits with their stress and anxiety. Conclusion: Despite this small sample size, this mindfulness meditation intervention did positively impact patient-report outcomes of HRQoL in this patient population, thereby larger randomized studies are warranted.